An unusual cause of facial burn. - Mazzotta, F. (European Journal of Pediatric Dermatology, 2023)
A 10-year-old boy was urgently examined due to the sudden appearance of burn lesions of the fronto-palpebral region. Physical examination showed linear and circinate burn lesions of the eyelids and frontal region. The medical history informed us that the lesions had appeared following the explosion of a “panzerotto” that the child was about to eat.